Comparative Study of Students’ Cognitive Learning Outcomes Between Boarding School and Home Living in Al-Qur’an Hadith Learning for Grade 5 at MI Ya Bakii 01 Kesugihan - Mayla Maslakahatun Nisa; Nani Kurniasih; Aldi Prasetyo; Ziyadul Haq Anniami; Putri Wahyuni (Universitas Muhammadiyah Enrekang, 2025)
MI Ya BAKII 01 Kesugihan is a madrasah where some of the students live in Islamic boarding schools and some live at home. With the existence of Islamic boarding schools, it is likely that students who live in Islamic boarding schools will be better and excel in learning the Qur'an and Hadith. However, it does not rule out the possibility that students who live at home are actually superior to students who live at home, due to several factors. The objectives of this study are 1) to determine the cognitive learning outcomes of grade 5, 2) to determine whether there are differences in the cognitive outcomes of students who live in Islamic boarding schools and students who live at home, 3) to determine what factors influence students' cognitive learning outcomes. This study uses a quantitative approach with a comparative type. The population in this study were 124 students of grade 5 MI Ya BAKII 01 Kesugihan. Furthermore, the data obtained were tested using the analysis prerequisite test with the normality test and the homogeneity test. The research data were tested using the independent sample T-test. Testing in the research showed that there was no significant difference in the scores of students who lived at home and students who lived in Islamic boarding schools.